2003
DOI: 10.1309/p5abr5kq89rnjtfh
|View full text |Cite
|
Sign up to set email alerts
|

p63 and TTF-1 Immunostaining: A Useful Marker Panel for Distinguishing Small Cell Carcinoma of Lung From Poorly Differentiated Squamous Cell Carcinoma of Lung

Abstract: We studied the usefulness of p63 and thyroid transcription factor-1 (TTF-1) immunostains for differentiating poorly differentiated squamous cell carcinoma (PDSCC) from small cell lung carcinoma (SCLC). We used monoclonal antibodies reactive to p63 or TTF-1 to stain 4-microns-thick sections from 30 formalin-fixed, paraffin-embedded lung biopsy and resection specimens and 7 alcohol-fixed, formalin-postfixed, paraffin-embedded cell blocks from lung fine-needle aspirations (FNAs). For p63, we used a streptavidin-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…Immunohistochemistry is helpful in distinguishing amongst these basaloid neoplasms [51,52]. SCCs express p63 and CK5/6, while neuroendocrine markers such as synaptophysin and chromogranin identify neuroendocrine carcinomas.…”
Section: Cytologic Diagnosis Of Hpv-associated Hnsccmentioning
confidence: 99%
“…Immunohistochemistry is helpful in distinguishing amongst these basaloid neoplasms [51,52]. SCCs express p63 and CK5/6, while neuroendocrine markers such as synaptophysin and chromogranin identify neuroendocrine carcinomas.…”
Section: Cytologic Diagnosis Of Hpv-associated Hnsccmentioning
confidence: 99%
“…A small cell variant of squamous cell carcinoma may mimic SCLC, particularly in biopsies where tell-tale signs of squamous differentiation are lacking. Staining for p63, combined with negativity for NE markers, is useful to establish the diagnosis36 (figure 9A,B).…”
Section: Small Cell Lung Carcinomamentioning
confidence: 99%
“…Various ICC antibody panels have been utilized for distinguishing SqC from AC, including CK7, CK5/6, 34βE12, p63, TTF-1, and napsin A [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32]. We found that TTF-1 and p63 as a limited panel can reliably subclassify NSCLC in the vast majority of cases.…”
Section: Discussionmentioning
confidence: 99%